Analisis Manajemen Risiko Konter Voucher dan Pulsa di Kecamatan Adiwerna, Tegal - Akbar Salafudin; Amirah (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study analyzes risk management in voucher and mobile phone credit counter businesses in Adiwerna District, Tegal Regency, focusing on risk identification, evaluation, and management strategies. The research method employed a descriptive approach, using primary data obtained through a Google Form questionnaire from 30 respondents, consisting of counter owners, employees, and distributors. The data collected included risk assessments based on frequency, probability, and impact. The results indicate that the most frequent risks are price competition and digital services (73.3%), technical risks such as power and internet outages (66.7%), supply disruptions from providers (60%), internal fraud (50%), and seasonal demand fluctuations (46.7%). Using a probability-impact matrix, technical risks are ranked "very high," followed by supply disruptions and internal fraud at "high-medium." Recommended mitigation strategies include diversifying supply sources, implementing a point-of-sale (POS) system, daily reconciliation, enhancing physical security, and utilizing digital technology. These findings are expected to help businesses improve operational resilience and provide practical recommendations for the development of micro-enterprises in the mobile phone credit and voucher service sector.